Los poetas gallegos ante Sancho Panza en 1905 - Alonso Montero, Xesús (Madrygal. Revista de Estudios Gallegos, 2005)
This work goes over again de admiration and interest that several poets in the 19th and 20th century show in the face of Sancho Panza like character. On the other hand, the work tries to recover the Galician authors´ creation about Cervantes themes.